Affinity probes based on small-molecule inhibitors for tumor imaging - Yi, Xinzeyu; Wang, Zheng; Hu, Xiang; Yu, Aixi (Frontiers in Oncology, 2022)
Methods for molecular imaging of target areas, including optical imaging, radionuclide imaging, magnetic resonance imaging and other imaging technologies, are helpful for the early diagnosis and precise treatment of cancers. In addition to cancer management, small-molecule inhibitors are also used for developing cancer target probes since they act as the tight-binding ligands of overexpressed proteins in cancer cells. This review aims to summarize the structural designs of affinity probes based on small-molecule inhibitors from the aspects of the inhibitor, linker, dye and radionuclide, and discusses the influence of the modification of these structures on affinity and pharmacokinetics. We also present examples of inhibitor affinity probes in clinical applications, and these summaries will provide insights for future research and clinical translations.